229k views
2 votes
Use the limit definition of the derivative to find the instantaneous rate of change of

f(x)=5x^2+3x+3 at x=4

User Zzk
by
6.4k points

1 Answer

1 vote


f'(4) = 43

Step-by-step explanation:

Given:
f(x)=5x^2 + 3x + 3


\displaystyle f'(x)= \lim_(h \to 0) (f(x+h) - f(x))/(h)

Note that


f(x+h) = 5(x+h)^2 + 3(x+h) + 3


\:\:\;\:\:\:\:= 5(x^2 + 2hx + h^2) + 3x + 3h +3


\:\:\;\:\:\:\:= 5x^2 + 10hx + 5h^2 + 3x + 3h +3

Substituting the above equation into the expression for f'(x), we can then write f'(x) as


\displaystyle f'(x) = \lim_(h \to 0) (10hx + 3h + 5h^2)/(h)


\displaystyle\:\:\;\:\:\:\:= \lim_(h \to 0) (10x +3 +5h)


\:\:\;\:\:\:\:= 10x + 3

Therefore,


f'(4) = 10(4) + 3 = 43

User Maksym Dudyk
by
6.1k points